Digital Administrative Innovation and Governance Transformation: An Evaluation of the E-Surat Program in Surabaya City - Mukidah, Mukidah; Pramudiana, Ika Devy; Roekminiati, Sri; Mustofa, Amirul (Socious Journal, 2025)
This study evaluates the effectiveness of the E-Surat program implemented by the Surabaya City Department of Industry and Manpower (Disperinaker) as a digital administrative innovation to enhance efficiency, accuracy, and transparency in internal correspondence. A descriptive qualitative approach was applied, combining in-depth interviews with employees, systematic observation, and document analysis. Campbell’s evaluation indicators goal achievement, system stability, and user satisfaction served as the analytical framework. Findings reveal that since its introduction in 2018, E-Surat has improved administrative workflows, reduced paper consumption, and accelerated document circulation. The system is reliable, supported by adequate infrastructure, and integrated into daily organizational routines. It strengthens transparency, accountability, and interdepartmental coordination, while user satisfaction remains high due to its accessibility, security features, and responsive technical support.Despite these achievements, challenges persist in enhancing digital literacy, technical capacity, and employee involvement in system development. Overall, the program meets key success indicators but requires ongoing capacity building and participatory improvements to function as a strategic enabler of adaptive and inclusive digital governance. This study contributes to digital governance scholarship by providing empirical evidence from local government innovation in Indonesia, illustrating how administrative digitalization can drive transparency and efficiency in developing contexts.